Sexual Violence Prevention and International Students in Canadian Universities: Misalignments, Gaps and Ways Forward - Todorova, Miglena S.; Brooks, Hayley H.; Persaud, Rachel S.; Moorhouse, Emily A. (Comparative and International Education / Éducation comparée et internationale, 2022)
This article reports findings from a qualitative study exploring how international students and campus staff in urban universities in Canada perceive sexual violence and prevention initiatives enacted in their university. The study rests upon personal interviews and three focus groups involving a total of 95 participants (64 students from 25 countries and 31 campus support staff members who work directly with these learners). The analysis of these narratives focuses on three pivotal areas in sexual violence prevention: awareness, incident reporting patterns, and fostering a “culture of consent.” It reveals important misalignment between the needs and knowledges of international students and the Western, ethnocentric cultural logic of campus approaches. Instead, international students seek peer-led discussions about gender inequality, sexuality, safe sex, and the role of religion, culture, and parents within their own communities and countries of origin. They also seek safe spaces to think through and debate the kind of politics or actions that could enable changes within their home countries and the world.